The other side of the story: challenges and opportunities in building sustainable online knowledge resources - Smith, Ailie (Circumscribere International Journal for the History of Science, 2018)
With more resources becoming freely available online through the digitisation projects and the publication of online public knowledge resources, the possibilities for connecting previously separate pieces of information have increased and some of the untold stories in the history of science can emerge. However there can be problems in relying on external knowledge services to connect pieces of the story. There are also gaps in the scientific biographies of many notable people, which may be filled by resources from other. This paper will explore some of the possibilities and challenges associated with producing and sustaining online knowledge resources.